The path to universal health coverage in five African and Asian countries: examining the association between insurance status and health-care use - Emily Odipo, MSc; Prashant Jarhyan, PhD; Jacinta Nzinga, PhD; Dorairaj Prabhakaran, ProfDM; Amit Aryal, MPH; Emma Clarke-Deelder, PhD; Sailesh Mohan, ProfPhD; Moshabela Mosa, ProfPhD; Munir Kassa Eshetu, MD; Todd P Lewis, PhD; Neena R Kapoor, MSc; Margaret E Kruk, ProfPhD; et al. (Elsevier, 2024)
Summary: Despite major efforts to achieve universal health coverage (UHC), progress has lagged in many African and Asian countries. A key strategy pursued by many countries is the use of health insurance to increase access and affordability. However, evidence on insurance coverage and on the association between insurance and UHC is mixed. We analysed nationally representative cross-sectional data collected between 2022 and 2023 in Ethiopia, Kenya, South Africa, India, and Laos. We described public and private insurance coverage by sociodemographic factors and used logistic regression to examine the associations between insurance status and seven health-care use outcomes. Health insurance coverage ranged from 25% in India to 100% in Laos. The share of private insurance ranged from 1% in Ethiopia to 13% in South Africa. Relative to the population with private insurance, the uninsured population had reduced odds of health-care use (adjusted odds ratio 0·68, 95% CI 0·50-0·94), cardiovascular examinations (0·63, 0·47-0·85), eye and dental examinations (0·54, 0·42-0·70), and ability to get or afford care (0·64, 0·48-0·86); private insurance was not associated with unmet need, mental health care, and cancer screening. Relative to private insurance, public insurance was associated with reduced odds of health-care use (0·60, 0·43-0·82), mental health care (0·50, 0·31-0·80), cardiovascular examinations (0·62, 0·46-0·84), and eye and dental examinations (0·50, 0·38-0·65). Results were highly heterogeneous across countries. Public health insurance appears to be only weakly associated with access to health services in the countries studied. Further research is needed to improve understanding of these associations and to identify the most effective financing strategies to achieve UHC.